2017
DOI: 10.1038/s41598-017-06535-y
|View full text |Cite
|
Sign up to set email alerts
|

Alantolactone induces apoptosis, promotes STAT3 glutathionylation and enhances chemosensitivity of A549 lung adenocarcinoma cells to doxorubicin via oxidative stress

Abstract: Alantolactone (ALT), a sesquiterpene lactone component of Inula helenium, has been reported to exert anticancer activity in various cancers. However, the cellular targets and underlying mechanism of anticancer activity of ALT in various cancers including lung cancer has not been fully defined. In the present study, we found that ALT effectively inhibits proliferation and triggers oxidative stress mediated-apoptosis in A549 lung adenocarcinoma cells by inducing ER stress and mitochondrial dysfunction. This ALT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 51 publications
7
82
1
Order By: Relevance
“…Live/dead assay was performed according to the protocol described previously. 18 Briefly, cells were seeded and treated in 6-well plates with Brv-A for 24 h in presence or absence of NAC. Cells were then washed twice with and re-suspended in PBS.…”
Section: Live/dead Assaymentioning
confidence: 99%
“…Live/dead assay was performed according to the protocol described previously. 18 Briefly, cells were seeded and treated in 6-well plates with Brv-A for 24 h in presence or absence of NAC. Cells were then washed twice with and re-suspended in PBS.…”
Section: Live/dead Assaymentioning
confidence: 99%
“…These enzymes have different origin, different physiological properties, different cell localisation, regulation, and catalytic mechanisms, yet they are all involved in the synthesis of the same PG (127,128). Earlier it was believed that mPGES2 was glutathione-independent, in contrast to the rest of the PGESs, but recent research has confirmed that mPGES2 binding activity is possible only in the presence of glutathione (101).…”
Section: Prostaglandin E2 Synthasesmentioning
confidence: 99%
“…The results showed that rapamycin signi cantly induced autophagy and reversed the effects of ALT on apoptosis, suggesting that ALT induces apoptosis partially through inhibition of autophagy. Necrosis, apoptosis and autophagy are three types of programmed cell death that are crucially involved in cancer cell progression, division and metastasis [23,24]. However, the relationship between autophagy and apoptosis remains incompletely understood.…”
Section: Discussionmentioning
confidence: 99%